Penggunaan Media Chatgpt Dalam Pembelajaran PAI Fase E - Ceceng Salamudin; Hikam Habibi Maulana (STAI Al-Musaddadiyah Garut, 2026)
This study is motivated by the challenges of Islamic Religious Education (PAI) learning at SMK Ciledug Garut, which remains largely theoretical, less interactive, and has not fully succeeded in enhancing student engagement and comprehension. The emergence of artificial intelligence tools such as ChatGPT offers a new approach to learning, particularly in the field of PAI, which has rarely been explored through digital innovation. The novelty of this study lies in the integration of ChatGPT as a learning aid in PAI for Phase E, with a specific focus on improving conceptual understanding, student interaction, and the attractiveness of learning materials.A qualitative research approach was employed, using observations, interviews, and document analysis as data collection techniques. Observations were conducted to examine the implementation of ChatGPT in the classroom, interviews with teachers and students explored their experiences, and document analysis was used to assess its impact on learning outcomes.The findings reveal that ChatGPT enhances students’ comprehension of PAI materials, increases active participation, and fosters a more engaging classroom environment. However, challenges such as limited internet access and the necessity of teacher guidance remain crucial factors influencing its effectiveness.In conclusion, this study highlights the significant potential of ChatGPT as an educational innovation in PAI learning. With proper integration strategies and active teacher support, this technology can strengthen the quality of religious education in the digital era. keywords: Chatgpt, PAI Learning